*This expression is the differences of cubes & the formula is...
(a - b)(a^2 + ab + b^2)
First: write the expression in lowest terms...
(b)(b)(b) - (2)(2)(2)
Sec: you need a term for the "a" and "b" variable in the formula >
"a" = b and "b" = 2
Third: place the terms in the corresponding variables...
(b - 2)(b^2 + b(2) + 2^2)
(b - 2)(b^2 + 2b + (2)(2))
(b - 2)(b^2 + 2b + 4)
2007-01-26 14:54:13
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
b^3 - 8 = (b - 2)(b^2 + 2b + 4)
2007-01-26 22:31:25
·
answer #2
·
answered by Sherman81 6
·
0⤊
0⤋
It is 0
b^3-8=0
b^3=8
b=2
2007-01-26 21:04:37
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
Not enough info given to solve for the answer.
2007-01-26 21:08:27
·
answer #4
·
answered by erbelgerbels 2
·
0⤊
1⤋
b³ = 8
b = ³\/8
b = ³\/2³
b = 2
><
2007-01-26 21:09:36
·
answer #5
·
answered by aeiou 7
·
0⤊
1⤋
cube root of eight
2007-01-26 21:04:14
·
answer #6
·
answered by Phillip 4
·
0⤊
2⤋
you need to know what goes in place of 'what'. if it's zero, b=2
2007-01-26 21:07:35
·
answer #7
·
answered by Spearfish 5
·
0⤊
1⤋